The challenge of eco-generativity. Embracing a positive mindset beyond eco-anxiety: a research agenda - Di Fabio, Annamaria; Svicher, Andrea (Frontiers in Psychology, 2024)
Climate change has emerged as a tough challenge affecting the world's society and economy in the twenty-first century. Furthermore, it has been determined that global warming and climate change have detrimental effects on human health both physical and psychological. In this framework, eco-anxiety has emerged as a new construct to assess the distress in relation to climate change and its effects. In the current article, after a study of the literature regarding both eco-anxiety and generativity related to environmental issues, in the search for a healthy response to eco-anxiety, we propose the construct of eco-generativity as a sustainable development-related concept for the health of planet earth and people in the present and in the future. Accordingly, we explore the definitions of generativity in relation to the ecological environment, examining the development of the concept in accordance with the most recent research. Subsequently, according to the lens of psychology of sustainability and sustainable development, we propose key elements of eco-generativity in terms of construct and measures. Finally, a research agenda for future research and intervention on eco-generativity is provided.